DIRECT TORQUE CONTROL OF MULTI-PHASE INDUCTION MOTOR WITH FUZZY LOGIC SPEED CONTROLLER - Listwan, Jacek (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2017)
The paper presents the Direct Torque Control with Space Vector Modulation (DTC-SVM) of seven-phase induction motor with Fuzzy Logic Speed Controller. The mathematical model of the seven-phase squirrel-cage induction motor and chosen methods of Space Vector Modulation have been presented. Simulation studies of the DTC-SVM with Fuzzy Logic speed controller have been carried out and the results of simulation studies have been presented and discussed. The author original contribution includes analysis and studies of considered control method of seven-phase induction motor.